Change of Accent as an Atypical Onset of non Fluent Primary Progressive Aphasia - Susy Paolini; Lucia Paciaroni; Antonio Manca; Roberto Rossi; Daniela Fornarelli; Stefano F. Cappa; Angela M. Abbatecola; Osvaldo Scarpino (Behavioural Neurology)
Language disorders can be the first symptom of many neurodegenerative diseases, including Alzheimer's disease (AD) and primary progressive aphasia (PPA). The main variants of PPA are: the non-fluent/agrammatic variant, the semantic variant and the logopenic variant.